Age-related change in the expression of NKCC1 in the cochlear lateral wall of C57BL/6J mice. (October 2014) - Liu, Yun; Chu, Hanqi; Chen, Jin; Zhou, Liangqiang; Chen, Qingguo; Yu, Yang; Wu, Zhengong; Wang, Shaoli; Lai, Yanbing; Pan, Chunchen; Cui, Yonghua
Abstract Conclusions: Na+-K+-2Cl– co-transporter isoform 1 (NKCC1) mRNA and protein decrease with increasing age in the cochlear lateral wall of C57BL/6J (C57) mice. The down-regulation of NKCC1 may influence the K+ transport efficiency and the homeostasis of ion transport cells, and cause the irreversible damage of cochlear cells in old C57 mice. Our results indicate that NKCC1 may play an important role in the pathogenesis of age-related hearing loss (AHL). Objectives: The aim of the present study was to investigate the relationship between the functional expression of NKCC1 transporter and the etiology of AHL. Methods: C57 mice were used and randomly divided into four groups according to age (4 weeks, 14 weeks, 26 weeks, and 52 weeks). Immunofluorescence technique, quantitative real-time PCR, and western blot were applied to detect the expression of NKCC1 in the cochlear lateral wall of C57 mice at the various ages. Results: In all four groups, the expression of NKCC1 was observed in the stria vascularis and type II fibrocytes of the spiral ligament. Also, the expression of NKCC1 appeared to decrease with age at both the transcriptional level and the protein level.